Access : introduction to travel and tourism - Mancini, Marc (Singapore : Thomson Learning Asia, 2006)
This is the first introductory textbook/workbook conceived to address the new realities of the travel industry. Access provides an overview of all sections of the business. The author has taken a highly practical approach, ensuring that readers acquire all the facts, insight and insider knowledge they must know to succeed in the travel industry. It is full of up-to-date, real-world industry terminology and can serve as a sturdy foundation for all future travel studies. Readers' will gain valuable insight into the implications of Internet travel sales. Questions for discussion and creative, entertaining activities reinforce the wealth of information contained within each chapter. Plus, an accompanying instructor's guide and computerized test bank make it easy for instructors to implement the text's content in the classroom.
Preface -- Chapter 1. Going Places: An Overview of the Travel Industry -- Chapter 2A. Ribbons in the Sky: The Air Transportation Industry -- Chapter 2B. Taking to the Skies: Airports, Airfares, and Air Tickets -- Chapter 3. Homes Away from Home: The Hospitality Industry -- Chapter 4. Dealing with Dreams: The Travel Agency Industry -- Chapter 5. Better by the Bunch: The Tour Industry Today -- Chapter 6. Magic at Sea: The Cruise Industry -- Chapter 7. Extra Specials: Other Segments of the Travel Industry -- Chapter 8. Making Connections: How to Market, Sell to, and Serve the Traveling Public -- Chapter 9. Here, There, Almost Anywhere: The Geography of Travel -- Chapter 10. This and That -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: TRAVEL